BS EN IEC 61249-2-51. Materials for printed boards and other interconnecting structures. Part 2-51. Reinforced base materials; clad and unclad. Base materials for Integrated Circuit card carrier tape; unclad (30th July 2021) - British Standards Institution,
No abstract available